Menstrual hygiene practices among the adolescent schoolgirls in the rural area of Bangladesh - Mst. Rokshana Rabeya; Md Nazrul Islam; Umme Hafsa; Nadiatul Ami Nisa; Gopal Kumar Ghosh; Afsana Yesmin; Khairun Nahar Juthi; Tamima Rahman; Tanjina Sharmin (Intelektual Pustaka Media Utama, 2022)
Adolescence is a time of tremendous opportunity. However, inadequate menstrual hygiene habits are related to lower academic achievement and enrollment at school, with possible effects on longer-term socio-economic status and impaired overall quality of life. Therefore, this cross-sectional study was conducted among 422 adolescent schoolgirls in Bangladesh between July 2019 and February 2020 with the aim of examining menstrual hygiene practices. Data indicate that the mean age of menarche in 422 adolescents was 12.71±0.97. According to the data, 47% had well, and 53% had poor hygiene practices. In multivariable logistic regression analysis, educational status of respondents’ mother at secondary level [AOR = 2.023, 95% CI: 1.159-3.532], fathers at graduate and above level [ AOR = 3.150, 95% CI: 0.883-11.238], high level of household income [AOR = 2.580, 95% CI: 1.480-4.495], and knowledge about complication of poor hygiene practice among girls [AOR = 2.286, 95% CI: 1.160-4.504] were significantly associated with the level of hygiene practices. Poor menstrual hygiene practice was found among more than half of girls. Attitude toward safe menstrual materials should initiate to improve good hygiene practices. Awareness campaigns for parents and teachers to assist their children would be a vital strategy to ensure good hygiene practices.